Proses Implementasi Kebijakan Lingkungan Dalam Pemanfaatan Limbah Kelapa Sawit Di Kabupaten Rokan Hulu - Dia Meirina Suri; Eka Komalasari (UIR Press, 2019)
The amount of waste from the management of oil palm plantations in Rokan Hulu Regency, besides having a negative impact on the environment and the community also has a positive impact, one of the positive impacts of palm oil plantation waste management is as an energy source that can be used for electricity. Utilization of palm oil waste is carried out in reference to environmental policies made by the government, this policy shows the government's attention to environmental conditions due to pollution of palm oil processing waste. The implementation of this policy was successfully carried out so as to provide benefits to the community, namely the existence of electricity that can be enjoyed by the community. This can be used as an example or model for other regions that also have extensive oil palm plantations. The purpose of this research is to see the process of implementing environmental policies in the utilization of palm oil waste capable of contributing electricity to the surrounding community. Data analysis uses a qualitative approach with data triangulation and is presented in a descriptive form. The results of the study found that in the implementation process as seen from the idealized policy, the target group, the implementing organization, environmental factors in Rokan Hulu Regency there was collaboration between the government and the community and with the private sector so that the implementation of environmental policies could be carried out and the results could be seen from the presence of PLTBg Providing electricity to residents in three villages, this policy can be said to be successful and can be a model for other areas that have large oil palm plantations.